Vanguardas em formação: as obras iniciais de Augusto de Campos e de Ferreira Gullar - Adilson Antonio Barbosa Junior (2015)
ABSTRACT This master's thesis presents a comparative analysis of Augusto de Campos' and Ferreira Gullar's early works in order to examine the gradual shaping of an avant-garde poetics. It tries to establish the way in which, in each poet, formal investigation, awareness in the handling of language, and innovative compositional procedures, themes and motives can already be observed in works written before the explicit adoption of an avant-gardist attitude. It also discusses the main meanings and variations of the word avant-garde, in particular that of neovanguard from mid-20th century, that is to say, the immediate context of these poets' upbringing.